Nanometer micropore heat insulation material for lithium battery energy storage cabinet and preparation method thereof

By using nano-microporous insulation materials in lithium battery energy storage cabinets, the problems of poor thermal insulation and poor temperature and fire resistance of existing insulation materials are solved, better high-temperature insulation and fire resistance are achieved, and compressive strength and compressive uniformity are improved.

CN119613080AInactive Publication Date: 2025-03-14ANHUI ZHONGHE THERMAL INSULATION MATERIAL MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311170252.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium battery energy storage cabinet insulation materials have poor thermal insulation, are not light and thin, and have poor temperature and fire resistance, which affects their use in lithium battery energy storage cabinets.

Method used

A nano-microporous thermal insulation material for lithium battery energy storage cabinets is used, and its raw materials include mixed vapor phase powder, aerogel powder, silicon carbide micro powder, composite whiskers, foam metal and glass whiskers, and is prepared by stirring, mixing and pressing molding.

Benefits of technology

This thermal insulation material transfers heat through conduction and convection at low temperatures, and heat transfers through radiation at high temperatures, improving the high-temperature thermal insulation and fire resistance of lithium battery energy storage cabinets, while enhancing compressive strength and compressive uniformity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004443669610000081
    Figure BDA0004443669610000081
Patent Text Reader

Abstract

The invention discloses a nano microporous thermal insulation material for a lithium battery energy storage cabinet, which is prepared from the following raw materials in parts by weight: 100 to 120 parts of mixed gas phase powder, 20 to 30 parts of aerogel powder, 10 to 20 parts of silicon carbide micro powder, 10 to 20 parts of composite whisker, 5 to 10 parts of foam metal and 1 to 10 parts of glass whisker. The invention also discloses a preparation method of the nano microporous thermal insulation material for the lithium battery energy storage cabinet. The preparation method comprises the following steps: (1) weighing raw materials; (2) mixing the raw materials, and stirring to obtain a mixture; and (3) pressing the mixture to obtain a blank plate, so as to obtain the nano microporous thermal insulation material for the lithium battery energy storage cabinet. The nanometer micropore heat insulation material for the lithium battery energy storage cabinet is good in compressive strength, high in compressive uniformity and good in heat insulation and fire resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery accessories and equipment, and in particular to a nano-microporous thermal insulation material for a lithium battery energy storage cabinet and a preparation method thereof. Background Art

[0002] With the rapid development of new energy technologies, a large number of new energy sources represented by photovoltaics and wind power have been connected to the power grid, causing a sharp increase in the demand for power grid frequency regulation and peak regulation resources. Electrochemical energy storage (lithium-ion) systems suitable for multiple scenarios have begun to be widely promoted and applied. Energy storage can be divided into pre-meter energy storage and post-meter energy storage according to different application fields. Pre-meter energy storage can be divided into power supply side energy storage and grid side energy storage, which belongs to power engineering investment projects. Post-meter energy storage includes industrial and commercial energy storage and household energy storage. Household energy storage is mainly used in home scenarios and presents certain electrification characteristics. Since battery energy storage systems have higher energy density, their application scenarios are more extensive. However, battery energy storage systems also have certain risks. The main risks of battery energy storage systems are battery damage or system overheating caused by internal failures or external fires. These failures will cause great safety hazards, such as the release of toxic or flammable gases, as well as the risk of fire and explosion. Therefore, passive insulation materials need to be installed inside the lithium battery energy storage cabinet. The existing insulation materials have poor thermal insulation, are not light and thin, or have unsatisfactory heat and fire resistance, which affects their use in lithium battery energy storage cabinets. Summary of the invention

[0003] In view of this, the present invention provides a nano-microporous thermal insulation material for a lithium battery energy storage cabinet and a preparation method thereof to solve the above-mentioned problems.

[0004] The technical solution adopted by the present invention to solve its technical problem is:

[0005] A nano-microporous thermal insulation material for a lithium battery energy storage cabinet. The raw materials of the nano-microporous thermal insulation material for a lithium battery energy storage cabinet include the following components by weight: 100-120 parts of mixed gas phase powder, 20-30 parts of aerogel powder, 10-20 parts of silicon carbide powder, 10-20 parts of composite whiskers, 5-10 parts of foam metals and 1-10 parts of glass whiskers.

[0006] Furthermore, the mixed gas phase powder includes gas phase silicon dioxide powder and gas phase aluminum oxide powder, the mass ratio of the gas phase silicon dioxide powder to the gas phase aluminum oxide powder is 1:1, the particle size of the gas phase silicon dioxide powder is 10 to 40 nm, and the particle size of the gas phase aluminum oxide powder is 10 to 30 nm.

[0007] Furthermore, the aerogel powder includes at least one of silicon aerogel powder, carbon aerogel powder and metal aerogel powder, and the particle size of the aerogel powder is 10 to 20 μm.

[0008] Furthermore, the particle size of the silicon carbide powder is 5 to 15 μm.

[0009] Furthermore, the composite whisker includes mullite whisker, desulfurized gypsum whisker, titanium boride whisker and potassium hexatitanate whisker, and the mass ratio of the mullite whisker, desulfurized gypsum whisker, titanium boride whisker and potassium hexatitanate whisker is 1-2:1-2:1:1.

[0010] Furthermore, the preparation method of the composite whisker comprises the following steps:

[0011] Mullite whiskers, desulfurized gypsum whiskers, titanium boride whiskers and potassium hexatitanate whiskers in a mass ratio of 1 to 2:1 to 2:1:1 are mixed and placed in a mixer, and stirred at a speed of 400 to 600 rpm for 20 to 30 minutes at room temperature to obtain composite whiskers.

[0012] Furthermore, the foam metal includes at least one of foam iron, foam copper, foam nickel, foam cobalt and foam titanium.

[0013] Furthermore, the glass whisker has a diameter of 1 to 3 μm and a length of 10 to 20 μm.

[0014] Furthermore, the method for preparing the nanoporous thermal insulation material for the lithium battery energy storage cabinet comprises the following steps:

[0015] (1) weighing and mixing gas phase powder, aerogel powder, silicon carbide powder, composite whisker, foam metal and glass whisker, drying them in sequence for later use;

[0016] (2) putting the mixed gas phase powder into a mixer, and sequentially adding aerogel powder, silicon carbide powder, composite whisker, foam metal and glass whisker, stirring and mixing evenly to obtain a mixture;

[0017] (3) Pour the uniformly dispersed mixture into a pressing mold and place it in a pressing machine for pressing and molding to obtain a nano-microporous thermal insulation material for a lithium battery energy storage cabinet.

[0018] Furthermore, the conditions for the compression molding in step (3) are a compression speed of 1 to 3 mm / s, a pressure of 1 to 3 MPa, and a holding time of 10 to 20 s.

[0019] The beneficial effects of the present invention are:

[0020] The present invention uses mixed gas phase powder as a base material, and adds aerogel powder, silicon carbide powder and composite whiskers to prepare nano-microporous thermal insulation materials for lithium battery energy storage cabinets. Since the gas phase silica and gas phase alumina in the mixed gas phase powder have very low thermal conductivity, and the aerogel powder has very low thermal conductivity, the thermal insulation performance of the thermal insulation material can be effectively guaranteed. However, the overall strength deviation of the mixed gas phase powder and the aerogel powder, therefore, adding a certain amount of composite whiskers can improve the strength of the thermal insulation material, and the whiskers can form a cross network inside the thermal insulation material, playing the role of skeleton and overlap, so that the integrity of the thermal insulation material is improved, thereby enhancing the compressive strength and compressive uniformity of the thermal insulation material. It can be seen from the heat transfer mode that the thermal insulation material mainly relies on conduction heat transfer and convection heat transfer at low temperatures, and mainly relies on radiation heat transfer at high temperatures. Therefore, in order to ensure that the material is easy to form while avoiding the increasing thermal conductivity of the material, silicon carbide powder is doped into the insulation material as an infrared sunshade, which can be used to scatter and reflect thermal radiation electromagnetic waves caused by high temperature and temperature difference under high temperature, thereby effectively improving the high-temperature thermal insulation performance and fire resistance of nano-microporous insulation materials for lithium battery energy storage cabinets. DETAILED DESCRIPTION

[0021] The preparation method of the nano-microporous thermal insulation material for the lithium battery energy storage cabinet of the present invention comprises the following steps:

[0022] (1) Mullite whiskers, desulfurized gypsum whiskers, titanium boride whiskers and potassium hexatitanate whiskers are mixed in a mass ratio of 1 to 2:1 to 2:1:1, placed in a mixer, and stirred at a speed of 400 to 600 rpm for 20 to 30 minutes at room temperature to obtain composite whiskers.

[0023] (2) Mixing fumed silicon dioxide powder with a particle size of 10 to 40 nm and fumed aluminum oxide powder with a particle size of 10 to 30 nm in a mass ratio of 1:1 to obtain a mixed fumed powder.

[0024] (3) Weigh 100 to 120 parts of mixed gas phase powder, 20 to 30 parts of aerogel powder with a particle size of 10 to 20 μm, 10 to 20 parts of silicon carbide powder with a particle size of 5 to 15 μm, 10 to 20 parts of composite whiskers, 5 to 10 parts of foamed metals, and 1 to 10 parts of glass whiskers with a diameter of 1 to 3 μm and a length of 10 to 20 μm, respectively, by weight, and set aside.

[0025] (4) The mixed gas phase powder is put into a mixer, and aerogel powder, silicon carbide powder, composite whisker, foam metal and glass whisker are added in sequence, and stirred and mixed evenly to obtain a mixture.

[0026] (5) Pour the uniformly dispersed mixture into a pressing mold and place it in a pressing machine, and perform pressing molding under the conditions of a pressing speed of 1 to 3 mm / s, a pressure of 1 to 3 MPa, and a holding time of 10 to 20 s to obtain a nano-microporous thermal insulation material for a lithium battery energy storage cabinet.

[0027] Wherein, the aerogel powder includes at least one of silicon aerogel powder, carbon aerogel powder and metal aerogel powder; the foam metal includes at least one of foam iron, foam copper, foam nickel, foam cobalt and foam titanium.

[0028] Example 1

[0029] The preparation method of the nano-microporous thermal insulation material for the lithium battery energy storage cabinet of this embodiment comprises the following steps:

[0030] (1) Mullite whiskers, desulfurized gypsum whiskers, titanium boride whiskers and potassium hexatitanate whiskers were mixed in a mass ratio of 1:1:1:1, placed in a mixer, and stirred at a speed of 400 rpm for 20 minutes at room temperature to obtain composite whiskers.

[0031] (2) Mix fumed silicon dioxide powder with a particle size of 10 nm and fumed aluminum oxide powder with a particle size of 10 nm in a mass ratio of 1:1 to obtain a mixed fumed powder.

[0032] (3) Weigh 100 parts of mixed gas phase powder, 20 parts of silicon aerogel powder with a particle size of 10 μm, 10 parts of silicon carbide powder with a particle size of 5 μm, 10 parts of composite whiskers, 5 parts of foamed iron, and 1 part of glass whiskers with a diameter of 1 μm and a length of 10 μm respectively by weight and set aside.

[0033] (4) The mixed gas phase powder is put into a mixer, and silicon aerogel powder, silicon carbide powder, composite whisker, foamed iron and glass whisker are added in sequence, and stirred and mixed evenly to obtain a mixture.

[0034] (5) Pour the uniformly dispersed mixture into a pressing mold and place it in a pressing machine, and perform pressing molding under the conditions of a pressing speed of 1 mm / s, a pressure of 1 MPa, and a holding time of 10 s to obtain a nano-microporous thermal insulation material for a lithium battery energy storage cabinet.

[0035] Example 2

[0036] The preparation method of the nano-microporous thermal insulation material for the lithium battery energy storage cabinet of this embodiment comprises the following steps:

[0037] (1) Mullite whiskers, desulfurized gypsum whiskers, titanium boride whiskers and potassium hexatitanate whiskers were mixed in a mass ratio of 1.5:1.5:1:1, placed in a blender, and stirred at a speed of 500 rpm for 25 minutes at room temperature to obtain composite whiskers.

[0038] (2) Mix fumed silicon dioxide powder with a particle size of 20 nm and fumed aluminum oxide powder with a particle size of 20 nm in a mass ratio of 1:1 to obtain a mixed fumed powder.

[0039] (3) Weigh 110 parts of mixed gas phase powder, 25 parts of carbon aerogel powder with a particle size of 15 μm, 15 parts of silicon carbide powder with a particle size of 10 μm, 15 parts of composite whiskers, 7 parts of foamed copper, and 5 parts of glass whiskers with a diameter of 2 μm and a length of 15 μm, respectively, by weight, and set aside.

[0040] (4) The mixed gas phase powder is put into a mixer, and carbon aerogel powder, silicon carbide powder, composite whisker, foam copper and glass whisker are added in sequence, and stirred and mixed evenly to obtain a mixture.

[0041] (5) Pour the uniformly dispersed mixture into a pressing mold and place it in a pressing machine, and perform pressing molding under the conditions of a pressing speed of 2 mm / s, a pressure of 2 MPa, and a holding time of 15 s to obtain a nano-microporous thermal insulation material for a lithium battery energy storage cabinet.

[0042] Example 3

[0043] (1) Mullite whiskers, desulfurized gypsum whiskers, titanium boride whiskers and potassium hexatitanate whiskers were mixed in a mass ratio of 2:2:1:1, placed in a mixer, and stirred at a speed of 600 rpm for 30 minutes at room temperature to obtain composite whiskers.

[0044] (2) Mix fumed silicon dioxide powder with a particle size of 40 nm and fumed aluminum oxide powder with a particle size of 30 nm in a mass ratio of 1:1 to obtain a mixed fumed powder.

[0045] (3) Weigh 120 parts of mixed gas phase powder, 30 parts of metal aerogel powder with a particle size of 20 μm, 20 parts of silicon carbide powder with a particle size of 15 μm, 20 parts of composite whiskers, 10 parts of foamed cobalt, and 10 parts of glass whiskers with a diameter of 3 μm and a length of 20 μm, respectively, by weight, and set aside.

[0046] (4) The mixed gas phase powder is put into a mixer, and metal aerogel powder, silicon carbide powder, composite whisker, foamed cobalt and glass whisker are added in sequence, and the mixture is stirred and mixed evenly to obtain a mixture.

[0047] (5) Pour the uniformly dispersed mixture into a pressing mold and place it in a pressing machine, and perform pressing molding under the conditions of a pressing speed of 3 mm / s, a pressure of 3 MPa, and a holding time of 20 s to obtain a nano-microporous thermal insulation material for a lithium battery energy storage cabinet.

[0048] Comparative Example 1

[0049] The preparation method of the nano-porous thermal insulation material for the lithium battery energy storage cabinet of this comparative example is substantially the same as the preparation method of Example 1, except that no aerogel powder is added to the thermal insulation material of this comparative example.

[0050] Comparative Example 2

[0051] The preparation method of the nano-porous thermal insulation material for the lithium battery energy storage cabinet of this comparative example is substantially the same as the preparation method of Example 1, except that silicon carbide powder is not added to the thermal insulation material of this comparative example.

[0052] Comparative Example 3

[0053] The preparation method of the nano-porous thermal insulation material for the lithium battery energy storage cabinet of this comparative example is substantially the same as the preparation method of Example 1, except that no composite whiskers are added to the thermal insulation material of this comparative example.

[0054] Experimental example

[0055] This test example provides the performance test of the thermal insulation materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3. The test method of the flexural strength of the thermal insulation material refers to GB / T 7019-2014; the aspect ratio calculation formula is: aspect ratio = transverse flexural strength / longitudinal flexural strength × 100%; the test method of the fire resistance limit refers to GB / T 9978.1-2008.

[0056] Table 1 Performance test results of thermal insulation materials of various embodiments and comparative examples:

[0057]

[0058] As can be seen from Table 1, the fire resistance limits of the nanoporous thermal insulation materials for lithium battery energy storage cabinets prepared according to the method of the present invention in Examples 1 to 3 are all over 450 minutes, indicating that the fire resistance of the nanoporous thermal insulation materials for lithium battery energy storage cabinets is good. The transverse flexural strength of the nanoporous thermal insulation materials for lithium battery energy storage cabinets prepared in Examples 1 to 3 is higher than 3.5 MPa, the longitudinal flexural strength is higher than 4.5 MPa, and the aspect ratio is greater than 75%, indicating that the thermal insulation materials prepared by the present invention have good compressive strength and high compressive uniformity.

[0059] Compared with Example 1, the transverse flexural strength, longitudinal flexural strength and fire resistance limit of the samples of Comparative Examples 1 to 3 are all lower than those of the sample of Example 1, which further illustrates that the nano-microporous thermal insulation material for lithium battery energy storage cabinets prepared by the method of the present invention can not only increase the fire resistance and heat insulation performance, but also improve the compressive strength and compressive uniformity of the thermal insulation material, and has good application prospects.

[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and additions without departing from the method of the present invention, and these improvements and additions should also be regarded as within the scope of the present invention.

Claims

1. A nano-microporous thermal insulation material for a lithium battery energy storage cabinet, characterized in that: The raw materials of the nano-microporous thermal insulation material for the lithium battery energy storage cabinet include the following components by weight: 100-120 parts of mixed gas phase powder, 20-30 parts of aerogel powder, 10-20 parts of silicon carbide powder, 10-20 parts of composite whiskers, 5-10 parts of foam metal and 1-10 parts of glass whiskers.

2. The nanoporous thermal insulation material for a lithium battery energy storage cabinet according to claim 1, characterized in that: The mixed gas phase powder comprises gas phase silicon dioxide powder and gas phase aluminum oxide powder, the mass ratio of the gas phase silicon dioxide powder to the gas phase aluminum oxide powder is 1:1, the particle size of the gas phase silicon dioxide powder is 10 to 40 nm, and the particle size of the gas phase aluminum oxide powder is 10 to 30 nm.

3. The nanoporous thermal insulation material for lithium battery energy storage cabinet according to claim 1, characterized in that: The aerogel powder includes at least one of silicon aerogel powder, carbon aerogel powder and metal aerogel powder, and the particle size of the aerogel powder is 10 to 20 μm.

4. The nanoporous thermal insulation material for lithium battery energy storage cabinet according to claim 1, characterized in that: The particle size of the silicon carbide powder is 5 to 15 μm.

5. The nanoporous thermal insulation material for lithium battery energy storage cabinet according to claim 1, characterized in that: The composite whisker comprises mullite whisker, desulfurized gypsum whisker, titanium boride whisker and potassium hexatitanate whisker, and the mass ratio of the mullite whisker, desulfurized gypsum whisker, titanium boride whisker and potassium hexatitanate whisker is 1-2:1-2:1:

1.

6. The nano-microporous thermal insulation material for lithium battery energy storage cabinet according to claim 5, characterized in that: The preparation method of the composite whisker comprises the following steps: Mullite whiskers, desulfurized gypsum whiskers, titanium boride whiskers and potassium hexatitanate whiskers in a mass ratio of 1 to 2:1 to 2:1:1 are mixed and placed in a mixer, and stirred at a speed of 400 to 600 rpm for 20 to 30 minutes at room temperature to obtain composite whiskers.

7. The nanoporous thermal insulation material for lithium battery energy storage cabinet according to claim 1, characterized in that: The foam metal includes at least one of foam iron, foam copper, foam nickel, foam cobalt and foam titanium.

8. The nano-microporous thermal insulation material for lithium battery energy storage cabinet according to claim 1, characterized in that: The glass whisker has a diameter of 1 to 3 μm and a length of 10 to 20 μm.

9. A method for preparing a nanoporous thermal insulation material for a lithium battery energy storage cabinet according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) weighing and mixing gas phase powder, aerogel powder, silicon carbide powder, composite whisker, foam metal and glass whisker, drying them in sequence for later use; (2) putting the mixed gas phase powder into a mixer, and sequentially adding aerogel powder, silicon carbide powder, composite whisker, foam metal and glass whisker, stirring and mixing evenly to obtain a mixture; (3) Pour the uniformly dispersed mixture into a pressing mold and place it in a pressing machine for pressing and molding to obtain a nano-microporous thermal insulation material for a lithium battery energy storage cabinet.

10. The method for preparing the nano-porous thermal insulation material for lithium battery energy storage cabinet according to claim 9, characterized in that: The conditions for the compression molding in step (3) are a compression speed of 1 to 3 mm / s, a pressure of 1 to 3 MPa, and a holding time of 10 to 20 s.